Determination of phase transition from nematic to isotropic state in carbon nano-balls' doped nematic liquid crystals by electrical conductivity-dielectric measurements - Okutan, M; San, SE; Basaran, E; Yakuphanoğlu, Fahrettin (Elsevier, 2005)
The phase transition in carbon nano-balls' doped nematic liquid crystals has been investigated by electrical conductivity-dielectric measurements. The results of electrical conductivity and dielectric constant as a function temperature and frequency indicate that a phase transition, which is of the first order, takes place from nematic state and isotropic state. The phase transition for E7 and E7/C60 samples takes place at 326 and 321 K temperatures, respectively. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: liquid crystal; conductivity; dielectric; phase transition